OPTIMIZATION OF ENERGY SYSTEMS BY TOPOLOGICAL MODELS - Draganov, B. (Енергетика і автоматика, 2016)
The foundations of the optimization of energy systems based on exergy analysis and topological constructions. Are given information about graph theory, the incidence matrix. An example of the optimization of energy- geothermal and heat pump systems .